Where Have All the General Internists Gone? - Bylsma, Wayne H. (Springer-Verlag, 2010)
BACKGROUND: A shortage of primary care physicians is expected, due in part to decreasing numbers of physicians entering general internal medicine (GIM). Practicing general internists may contribute to the shortage by leaving internal medicine (IM) for other careers in and out of medicine. OBJECTIVE: To better understand mid-career attrition in IM. DESIGN AND PARTICIPANTS: Mail survey to a national sample of internists originally certified by the American Board of Internal Medicine in GIM or an IM subspecialty during the years 1990 to 1995. MAIN MEASURES: Self-reported current status as working in IM, working in another medical or non-medical field, not currently working but plan to return, or retired; and career satisfaction. KEY RESULTS: Nine percent of all internists in the 1990–1995 certification cohorts and a significantly larger proportion of general internists (17%) than IM subspecialists [(4%) P < 0.001] had left IM at mid career. A significantly lower proportion of general internists (70%) than IM subspecialists [(77%) (P < 0.008)] were satisfied with their career. The proportion of general internists who had left IM in 2006 (19%) was not significantly different from the 21% who left in 2004 (P = 0.45). The proportion of general internists who left IM was not significantly different in earlier (1990–92; 19%) versus later (1993–95; 15%) certification cohorts (P = 0.15). CONCLUSIONS: About one in six general internists leave IM by mid-career compared to one in 25 IM subspecialists. Although research finds that doctors leave medicine because of dissatisfaction, this study was inconclusive about whether general internists left IM in greater proportion than IM subspecialists for this reason. A more likely explanation is that GIM serves as a stepping stone to careers outside of IM.